PENINGKATAN HASIL BELAJAR MEMBACA BESERTA MAKNA AYAT SUCI AL-QUR’AN DALAM SURAT PENDEK PILIHAN MELALUI PENYUNTING SEBAYA - lili, Ha (Universitas Panca Marga, 2020)
Religion has a very important role in human life. Religion becomes a guide in the effort to create a meaningful, peaceful and dignified life. Realizing the importance of the role of religion for human life, internalization of religious values in the life of each individual becomes a necessity, which is pursued through education both in family, school and community circles. This research was conducted in 2 (two) cycles each cycle of two meetings. . The first cycle of the first meeting was on January 11 and the second meeting was on January 14, 2017. The second cycle of the first meeting was on February 1 and the second meeting was on February 4, 2017 using student activity instruments and teacher activity instruments in learning, as well as student learning outcomes instruments. The results of the study using the Peer Editor by paying attention to the appropriate learning steps in managing learning for the teacher and the existence of a cycle to the next cycle, classically the level of completeness is 93.33% greater than classical, which is 85%, meaning that learning through peer editing can well implemented.Keywords: Reading Meanings, Editors, Peers